It's Not What You Say, But How You Sound: CEO Vocal Masculinity and the Board's Early‐Stage CEO Compensation Decisions. (14th October 2021) - Nair, Krishnan; Haque, Waqas; Sauerwald, Steve
Abstract: Growing research in evolutionary psychology suggests that having a deep, masculine voice is beneficial to males in leadership positions because it signals physical strength. However, how this phenomenon plays out at the top of the modern organization is not clearly understood. We posit that CEO vocal masculinity positively influences early‐stage CEO compensation for male CEOs by biasing directors' perceptions of CEO quality. Challenging the pervasive notion that evolved biases are deterministic, we also examine how environmental conditions (i.e., industry competitiveness) and audience characteristics (i.e., female representation on the compensation committee) moderate the effect of CEO vocal masculinity. Longitudinal analyses on a unique dataset consisting of interviews and speeches of male CEOs from publicly listed UK firms provide support for our hypothesized predictions.